2015
DOI: 10.1002/anie.201508783
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx Engineering with a Recycling Glycopolymer that Increases Cell Survival In Vivo

Abstract: Synthetic glycopolymers that emulate cell-surface mucins have been used to elucidate the role of mucin overexpression in cancer. However, because they are internalized within hours, these glycopolymers could not be used to probe processes that occur on longer time scales. Here, we tested a panel of glycopolymers bearing a variety of lipids to identify those that persist on cell membranes. Strikingly, we found that cholesterylamine (CholA)-anchored glycopolymers are internalized into vesicles that serve as depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 35 publications
8
109
2
1
Order By: Relevance
“…Persistent and stable display of synthetic ligands is crucial for cell-surface engineering techniques to probe biological processes that occur on longer times scales. 10,15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent and stable display of synthetic ligands is crucial for cell-surface engineering techniques to probe biological processes that occur on longer times scales. 10,15 …”
Section: Resultsmentioning
confidence: 99%
“…16 It provides a powerful means to elucidate molecular mechanisms by which specific biomolecules perform their functions and may find application in cell therapy by targeting therapeutic cells to specific tissues, 2,79 endowing cells with new functions such as recruiting/restoring protein binding or directing cell signaling or stem cell differentiation, 1013 and altering immune cell responses toward cancerous cells. 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…We previously found that this particular lipid confers a long cell surface residence time to glycopolymer conjugates by mediating continuous recycling from an internal reservoir. (Woods et al, 2015) The core of the glycopolymer comprises N-acetylgalactosamine (GalNAc) residues affixed to a poly (methyl vinyl ketone [MVK]) backbone via oxime linkages. The spacing afforded by this structure approximates that of GalNAc-a-Ser/Thr clusters within native mucins.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some lipid-conjugated agents undergo rapid endocytosis (Capicciotti et al, 2017; Rabuka et al, 2008). Once internalized, the species may be degraded, become trapped within endosomes, or incorporated into intracellular membranes, making them inaccessible for mediating cell-cell interactions (Dutta et al, 2011a; Woods et al, 2015). …”
Section: Perspectivementioning
confidence: 99%